Recurrent tracheoesophageal fistula [Tekrarlayan trakeoözofageal fistul] - (:unkn) unknown (My University, 2009)
Aim: Recurrent tracheooesophageal fistula (rTEF) is a post operative complication of esophageal atresia (EA) with TEF. The diagnosis and treatment of recurrent TEF continues to be a contraversial problem. Material and Methods: Ten patients with the diagnosis of rTEF were evaluated and treated between October 1989 and July 2009. In this study we retrospectively analysed the clinical findings, diagnosis and treatment modalities of these patients. Results: There were six male and four female patients. The average age of the patients was 4.7 years. All patients had respiratory problems, while five had advanced recurrent pulmonary infections. Fluoroscopic evaluation revealed rTEF in 6 out of 9 patients. In seven patients endoscopy was performed and the fistula could be demonstrated with various methods. In three patients we tried to ligate the rTEF using endoscopic methods without any success. Fistula ligation was performed with a toracotomy in nine patients. In two patients pulmonary resection was performed due to advanced pulmonary damage. In two patients, rTEFs were ligated successfully in a second operation. Conclusion: Recurrent TEF is a complication of EA with TEF operations. Fluoroscopic studies do not always demonstrate rTEF. Endoscopy are more successful in demonstrating rTEF but again not in all cases. In some patients rTEF cannot be demonstrated in the early postoperative period, and some occur during a long- term follow up. Endoscopic treatment failed in all cases. We advice open surgery for rTEF patients.
Keywords: Esophageal atresia; Tracheoesophageal fistula